Study of multiple draw-zone interaction in block caving mines by means of a large 3D physical model - Trueman, R.; Castro, R.; Halim, Adrian (Pergamon, 2008)
Current production level design guidelines in block caving mines are based on the concept of interaction of movement zones and the spacing of draw-points at which mass flow is achieved. The limit of the isolated movement zone (IMZ) interaction has been determined by observations of the flow of sand and finely fragmented caved rock. This paper presents a study of the mechanisms and limit of IMZ interaction in coarse fragmented caved rock using a large 3D physical model. Results showed that when drawing from multiple drawpoints, the unmoved zone between IMZs is characterised by an increase in vertical load and a decrease in horizontal load. However, it was observed that the unmoved zones between the movement zones of adjacent draw-points did not enter the flow zone, despite drawpoints being spaced at less than 1.2 times the width of the IMZ. This result is in marked contrast to previous findings obtained in sand models, where movement zones have been observed to interact at draw-point spacings up to 1.5 times the width of the IMZ. The major reasons for the differences between the two different model results was found to be that significant stress arching and less induced vertical stress during flow was observed in the gravel model, in contrast to limited stress arching and more induced vertical stress in the sand models. It is hypothesised that significant stress arching would occur in block caving mines, and therefore that the results obtained in the gravel model maybe more representative of full-scale conditions. Movement zones in block caving mines may therefore not interact at draw-point spacings greater than the width of the isolated movement zone.